AB0185 INTERFERON-Γ AMPLIFIES IMMUNE RESPONSE MEDIATED BY TYPE I INTERFERONS IN PAEDIATRIC SYSTEMIC LUPUS ERYTHEMATOSUS AND CORRELATES WITH DISEASE ACTIVITY. (June 2019) - Moneta, Gian Marco; Bracaglia, Claudia; Caiello, Ivan; Pecoraro, Raffaele; Farroni, Chiara; Basta, Fabio; Bracci-Laudiero, Luisa; Carsetti, Rita; Benedetti, Fabrizio De; Marasco, Emiliano
Abstract : Background: Paediatric systemic lupus erythematosus (pSLE) is an autoimmune disorder of childhood characterized by the production of autoantibodies against nuclear antigens. In the last decade, several studies showed an up-regulation of genes induced by type I interferons (IFNα) in peripheral blood and tissues of pSLE patients 2 . It has been reported that the expression of this group of genes, known as the type I IFN signature, correlates with disease activity 2 . More recently, also the type II interferon (IFNγ) has been implicated in pSLE; however, its precise role has not been clarified yet 3 . Objectives: To investigate the role of IFNγ in the pathogenesis of pSLE evaluating: 1) the expression levels of IFNγ-related genes in the peripheral blood of pSLE patients; 2) the possible cross-talk between IFNγ and type I IFNs. Methods: Expression levels of IFNα-induced genes (IFI27, IFI44L, IFIT1, RSAD2, ISG15, SIGLEC1), IFNγ-induced genes (CXCL9, IDO1) and IFNγ itself were analysed by quantitative PCR (qPCR) in whole blood of pSLE patients and healthy donors (HDs). We developed a type II IFN score similarly to the type I IFN score described by Crow 4 . Peripheral blood mononuclear cells (PBMCs) from 6 HDs were stimulated in vitro with recombinant human IFNγ and IFNα2b; gene expression was evaluated by qPCR. CXCL9 and CXCL10 in sera and supernatants from stimulated cells were measured by ELISA. Whole blood of pSLE patients and HD was incubated with an anti-IFNγ neutralizing antibody and isotype control, and later type I and type II signatures were assessed. For each patient, SLEDAI was calculated. Results: Expression levels of both IFNα-induced genes, IFNγ-induced genes and IFNγ were upregulated in pSLE patients with active disease (n = 21) compared to HDs and pSLE patients with inactive disease (n = 17). The type II IFN score correlated with the SLEDAI ( r = 0.64, P < 0.01). As previously reported, also the type I IFN score correlated with SLEDAI ( r = 0.67, P < 0.01). We also found increased serum levels of CXCL9 and CXCL10 in pSLE patients compared to HDs ( P < 0.05). In order to study a possible crass-talk between type I and type II IFNs, we stimulated in vitro HD PBMCs with recombinant IFNα2b and IFNγ for 6 hours: we analysed the expression levels of type I and type II IFN signatures and assessed the production of CXCL9 and CXCL10 in the supernatants. IFNα2b strongly up-regulated the expression of IFNγ, CXCL9 and IDO1. On the other hand, IFNγ induced the expression of the 6 IFNα-related genes. IFNγ, but not IFNα2b, induced the release of CXCL9 in supernatants. Both IFNγ and IFNα2b induced the production of CXCL10. IFNγ also up-regulated the expression levels of both TLR7 and TLR9, two potent inducer of IFNα. Finally, whole blood of pSLE was incubated with an anti-IFNγ neutralizing antibody for 24 hours: the type II signature was significantly downregulated ( P < 0.05), whereas the type I signature was reduced without reaching statistical significance. Conclusion: Our data suggest a potential role of IFNγ in the pathogenesis of pSLE. IFNγ-induced genes in whole blood and CXCL9 in serum are increased in pSLE patients. Type I and type II signatures are not strictly interferon-specific as IFNγ can induce the expression of type I genes. Moreover, blocking of IFNγ in the blood of pSLE patients reduces the type II signature confirming the presence of IFNγ in the blood of pSLE patients. IFNγ also induces the expression of TLR7 and TLR9, and IFNα induces the expression of IFNγ, thus establishing a positive crosstalk between IFNα and IFNγ that potentiate their reciprocal biological activity in pSLE. References: [1] Petri M, et al. Lupus. 2009Oct;18:980-9. [2] Munroe M, et al. Ann Rheum Dis2016;75:2014-2021. [3] Rice GI, et al. Lancet Neurol2013;12:1159-69. Disclosure of Interests: Gian Marco Moneta: None declared, Claudia Bracaglia: None declared, Ivan Caiello: None declared, Raffaele Pecoraro: None declared, Chiara Farroni: None declared, Fabio Basta: None declared, Luisa Bracci-Laudiero: None declared, Rita Carsetti: None declared, Fabrizio De Benedetti Grant/research support from: Abbvie, SOBI, Novimmune, Roche, Novartis, Sanofi, Pfizer, Emiliano Marasco: None declared